1995
DOI: 10.1128/jb.177.17.5035-5039.1995
|View full text |Cite
|
Sign up to set email alerts
|

MalY of Escherichia coli is an enzyme with the activity of a beta C-S lyase (cystathionase)

Abstract: The Escherichia coli maltose system consists of a number of genes whose products are involved in the uptake and metabolism of maltose and maltodextrins. MalT is the central positive gene activator of the regulon and is, together with the cyclic AMP-catabolite gene activator protein system, necessary for the expression of the maltose genes. Expression of malY, a MalT-independent gene, leads to the repression of all MalT-dependent genes. We have purified MalY to homogeneity and found it to be a pyridoxal-5-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 28 publications
(23 reference statements)
2
93
0
Order By: Relevance
“…Like the Cdl protein, Fn1220 showed no significant homology with bC-S lyase, which catalyses the a,belimination of L-cysteine to produce H 2 S, pyruvate and ammonia. Instead, a database analysis demonstrated that the amino acid sequence of Fn0625 was 29-40 % identical with the bC-S lyase proteins encoded by malY in E. coli (Zdych et al, 1995), ytjE in Lactococcus lactis (MartinezCuesta et al, 2006;Sperandio et al, 2005), hly in Treponema denticola (Chu et al, 1995) and lcd in streptococcal species Yoshida et al, 2003Yoshida et al, , 2008. To identify the Fn0625 and Fn1220 proteins in the crude enzyme extracts of strain ATCC 25586, the recombinant proteins were purified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Like the Cdl protein, Fn1220 showed no significant homology with bC-S lyase, which catalyses the a,belimination of L-cysteine to produce H 2 S, pyruvate and ammonia. Instead, a database analysis demonstrated that the amino acid sequence of Fn0625 was 29-40 % identical with the bC-S lyase proteins encoded by malY in E. coli (Zdych et al, 1995), ytjE in Lactococcus lactis (MartinezCuesta et al, 2006;Sperandio et al, 2005), hly in Treponema denticola (Chu et al, 1995) and lcd in streptococcal species Yoshida et al, 2003Yoshida et al, , 2008. To identify the Fn0625 and Fn1220 proteins in the crude enzyme extracts of strain ATCC 25586, the recombinant proteins were purified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MalY is an enzyme with cystathionase activity. This activity is not required for repression; a mutant lacking the enzymatic activity still shows repressor activity (44). On the other hand, mutants can be isolated that exhibit normal cystathionase activity but are defective in their repressor activity (10).…”
mentioning
confidence: 95%
“…Of these enzymes, only AecD from C. glutamicum acts physiologically as a cystathionine b-lyase (Ruckert et al, 2003). PatB from B. subtilis (Auger et al, 2005) and MalY from E. coli (Zdych et al, 1995) can catalyse cystathionine b-elimination poorly, while their native activities and physiological roles are unknown.…”
Section: Phylogeny Of the Sulfurylation Enzymesmentioning
confidence: 99%